Financial and institutional sustainability of development projects: the case of the Green Corridor Project and the case of the High Dam Lake Area Project - Fawzy, Nadine Hisham (AUC Knowledge Fountain, 2012)
This study aims to discuss the negative implications of the narrow scope adopted by many donor agencies when addressing sustainability for development projects implemented in developing countries. This has resulted in a very limited impact when it comes to official development assistance (ODA). The study explores the main challenges facing the sustainability of local community development projects in specific; explores attempts to address those challenges; and then presents a more sustainable approach that is based on robust financial and institutional pillars. It argues that the introduction of such pillars creates a new approach to local community development projects that enhance their sustainability. The methodology adopted to prove this hypothesis depended on two case studies for two development projects in Egypt; The Green Corridor Project undertaken by the Italian Development Cooperation Agency, and The High Dam Lake Area Project implemented jointly by the Egyptian Ministry of Agriculture and Land Reclamation and the World Food Program (WFP). Through those case studies, a comparative analysis was conducted to examine how those financial and institutional pillars have affected the sustainability of the former project where they were introduced vis-ÃƒÆ’Ã‚Â -vis the latter where ignoring those aspects prevented this project from becoming sustainable. The study was able to reveal how donor agencies tend to deal with sustainable development as a fixed objective, rather than address its dynamic features. This is what the study introduces through an approach to local community development that sets in place immune structures resembled in robust local community institutions, in addition to enhancing local capacities that enable the community to handle their resources in a manner that allows them to explore various sustainable livelihoods options in pursuit of their own development.